71.5k views
1 vote
1. Evaluate -3x^3 -2y^2 when x=-5 and y =3

2. h^2-3h+2 when h=-2



Could use some help right now.

User Mkayaalp
by
4.7k points

2 Answers

5 votes

Answer:

357

Explanation:

A) We replace x = - 5 and u = 3 into -3x^3 -2y^2

and we have -3x^3 -2y^2= -3*(-5)^3 -2*3^2= -3*(-125)- 2*9

or -3x^3 -2y^2 = 375-18= 357

The answer is 357.

B) Replace h = -2 into h^2-3h+2

we have h^2-3h+2 = (-2)^2 -3*(-2) +2 = 4 +6 + 2= 12

The answer is 12

Have a good day.

User Michael Douma
by
5.0k points
5 votes

Answer:

357

Explanation:

A) We replace x = - 5 and u = 3 into -3x^3 -2y^2

and we have -3x^3 -2y^2= -3*(-5)^3 -2*3^2= -3*(-125)- 2*9

or -3x^3 -2y^2 = 375-18= 357

The answer is 357.

B) Replace h = -2 into h^2-3h+2

we have h^2-3h+2 = (-2)^2 -3*(-2) +2 = 4 +6 + 2= 12

The answer is 12

Have a good day.

User Kristopher Johnson
by
5.2k points